2019
DOI: 10.1177/0143034319849621
|View full text |Cite
|
Sign up to set email alerts
|

School factors and anxiety disorder among Hispanic youth: Results from the 2016 US National Survey on Children’s Health

Abstract: Anxiety disorders continue to be a major mental health problem among Hispanic youth. A greater understanding of particular risk factors among this at-risk population may assist school health professionals in developing psychosocial interventions designed to mitigate this growing problem. The present study evaluated a variety of school factors related to anxiety among a national sample of Hispanic youth in the US. A secondary analysis of the 2016 National Children’s Health Survey was conducted. A total of 2,138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The association between homework and psychological ill-being outcomes was investigated in four cross-sectional studies and one longitudinal study. Incomplete homework and longer homework durations were associated with a higher risk of anxiety symptoms [ 91 , 92 ], negative emotions [ 93 95 ] and even psychological distress in adulthood [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between homework and psychological ill-being outcomes was investigated in four cross-sectional studies and one longitudinal study. Incomplete homework and longer homework durations were associated with a higher risk of anxiety symptoms [ 91 , 92 ], negative emotions [ 93 95 ] and even psychological distress in adulthood [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…As we reviewed above, heavy academic burden exists as an important school-related stressor for students [ 91 , 92 , 94 96 ], probably due to excessive examinations [ 97 99 ] and unsatisfactory academic performance [ 100 102 ]. Actually, extrinsic cultural factors significantly impact upon student academic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Schools represent a structure in which adolescents develop their academic skills, and prosocial behaviors and tendencies, and are exposed to various factors that may enhance or impair their psychological development (Yockey et al, 2019). Bowden et al (2019) found that school-based interventions that draw on existing structural support offered by school communities may be an option for targeting suicide prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Though not reported to the same degree as their non-Hispanic counterparts, Hispanic youth experience high rates of anxiety and depressive symptoms. Previous studies indicate that 11%–29% of Hispanic youth experience anxiety (Potochnick & Perreira, 2010 ; Yockey et al, 2019 ), and 7%–22% experience depressive symptoms (Potochnick & Perreira, 2010 ; Saluja et al, 2004 ). Further, it has been found that Hispanic girls are more likely to experience depressive and anxiety symptoms (Gudiño & Lau, 2010 ; Lorenzo-Blanco et al, 2011 ; McLaughlin et al, 2007 ).…”
mentioning
confidence: 99%
“…There are potentially multiple sources of anxiety and depression for Hispanic youth, especially in the school setting. By being a victim of physical bullying, verbal bullying, feeling unsafe in school, and lacking social acceptance and social support (Stapinski et al, 2014 ; Yockey et al, 2019 ), school becomes a threatening environment and triggers the cycle of anxiety. Stereotype threat may also be part of this cycle of anxiety.…”
mentioning
confidence: 99%